Genetic studies as a tool for identifying novel potential targets for treatment of COPD. Issue 5 (30th November 2017) - Manichaikul, Ani; Nguyen, Jennifer N.
Chronic obstructive pulmonary disease (COPD), characterised by chronic airflow limitation and abnormal response to noxious particles or gases [1], is currently the fourth leading cause of death worldwide [2] and the only major cause of death that has seen continued increases in recent years. While smoking cessation, oxygen therapy and bronchodilators offer some relief from the symptoms of disease, and medications are available to prevent COPD exacerbations [3], there are currently no treatments available to slow or stop progression, reflecting a limited understanding of the molecular underpinnings of the disease. In this issue of the European Respiratory Journal, Obeidat et al. [4] identify surfactant protein-D (SP-D) as a potentially causal risk factor for COPD. Their paper is presented in multiple distinct parts, beginning with a genome-wide association study (GWAS) to identify single-nucleotide polymorphisms (SNPs) from three genomic regions (on chromosomes 6, 10 and 16) associated with circulating levels of SP-D, followed by a Mendelian randomisation study demonstrating that genetically determined lower levels of SP-D are associated with increased risk of COPD based on results from a large-scale consortium based on a GWAS of up to ∼11 000 COPD cases and ∼37 000 controls recently published by the International COPD Genetics Consortium [5]. The results from the study of Obeidat et al. [4] are promising and open new potential avenues for early diagnosis and treatment of this disease. How did we get to this novel finding, what steps remain to carry this finding forward towards establishing the role of SP-D in COPD, and how can we stimulate additional discovery of novel therapeutic targets? Genetic studies are a useful tool for identification of novel causal biomarkers and therapeutic targets for COPD http://ow.ly/zZKC30fNecz